Spiritual Handholds on Life - Fagg, Fred D. (Fred Dow) (Tufts Archival Research Center, 2006)
Fred Fagg recalls a moment when his life was saved by a handhold at the edge of a cliff and uses this story to explain the importance of his own "spiritual handholds."